Building Sanctuary: The Movement to Support Vietnam War Resisters in Canada, 1965-73 - Powell, Christopher (Labour / Le Travail, 2014)
The article reviews the book, "Building Sanctuary: The Movement to Support Vietnam War Resisters in Canada, 1965-73," by Jessica Squires.
Keywords: BUILDING Sanctuary: The Movement to Support Vietnam War Resisters in Canada 1965-1973 (Book); Canada; Nonfiction; PEACE movements; SQUIRES, Jessica; VIETNAM War, 1961-1975 -- Draft resisters